Um gole prá o santo, uma reza prá Deus : a festa de São Pedro de Heliópolis-BA (1985-2005) - Castro, Felipe Souza (2023)
The present study aims to analyze the process of creating the São Pedro festival in the municipality of Heliópolis/BA, taking into account the formation of the municipality and the construction of cultural identity. The festival was created after the emancipation of the municipality and since then, it has become an important tradition that represents the cultural identity of the region. This event is considered one of the largest held in the city, as it involves both sacred and profane elements. The festival of São Pedro de Heliópolis/BA was not an event thought up and idealized by the city's residents themselves, but by the then mayor José Emídio Tavares de Almeida, known by the local population as Zé do Sertão. In this sense, the party arose from someone's will, to produce effects on a community, since it comes to represent the identity of the municipality. It is from the process of creating the party that the problem for the development of this research arises: as a party designed and/or idealized by the public authorities, it was incorporated by the local community and becomes one of the main representations of the cultural identity of the municipality of Heliópolis/BA? How does the party impact the home and the street, that is, private and public life? How is society structured around the party? In this context, it is noted that in private life, the party is seen as an opportunity to gather family and friends, share typical food from the region and experience a moment of effervescence with the profane. In public life, the festival is seen as a moment of affirmation of the municipality's cultural identity, where residents show visitors the richness of their culture.